THE EFFECT OF PRODUCT QUALITY, SERVICE QUALITY, CUSTOMER VALUE ON CUSTOMER SATISFACTION AND WORD OF MOUTH - RACHMAN, AFIF SYAIFUL (JOURNAL OF RESEARCH IN MANAGEMENT, 2018)
This study aims to find out "The Effect of Product Quality, Service Quality, Customer Valueon Customer Satisfaction and Promotion of Mouth to Mouth". The population in this studywere Telkom customers of IndiHome. This study uses a sample of 150 respondents. Thesampling technique was carried out by convenience sampling method. Data analysis usespath analysis. The results of the analysis show that product quality, service quality,customer value have positive effect on the customer satisfaction of Telkom IndiHome,Purwokerto, (2) Service quality has a positive effect on the customer satisfaction and wordof mouth